UPAYA MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA DALAM MATERI MEMBACA DENGAN METODE ROLE PLAYING DI KELAS XI SEKOLAH LUAR BIASA NEGERI SUKANAGARA KABUPATEN CIANJUR - Uce Solihati (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2021)
Child with Intelectual Disability (ID) is a child below average intelligence, experiences behavioral obstacles, adjustments and occurs during his development. Childrens with Intellectual Disability are often equated with mentally retardation terms (Feeble Minded). Reading using the role playing method is one of the main lessons that teachers give to children at school. The lesson, which is a part of Bahasa course, is given early as a basis for further learning. Children who cannot read yet have difficulty following other lessons. The purpose of this classroom action research is entitled " Efforts to Improve Achievement of Learning Indonesian in Reading Material by Applying the Role Playing Method in Class XI SLB Negeri Sukanagara, Cianjur Regency " is to get an overview of the implementation of learning Indonesian in reading in children at SMPLB SLB N Sukanagara, Cianjur Regency and the difficulties faced by the teacher. in improving the implementation of learning to read in mentally retarded children. In this classroom action research the subjects of this study were five students with in class XI and the data collection techniques used were observation and test. Furthermore, the research results were analyzed using quantitative and qualitative analysis techniques.